SEMINAR PENYULUHAN HUKUM KENAKALAN REMAJA SEBAGAI SARANA PEMBERDAYAAN HUKUM WARGA DESA SUKOMORO - Nishfi Sya'bana, Laili; Dwi Setiawan, Ahmad; Nur Rachmat, Firdho Razaq; Hidayatulloh, M. Fahmi; Nadziroh, Qoniatun; Anjuni, Windy; Surur, Shobihus (LPPM UNHASY, 2025)
Based on research findings, it was found that one of the main factors driving juvenile delinquency is the less than optimal role of parents as role models or exemplars for their children. Additionally, characteristics such as selfishness and a tendency to inflate self-esteem also appear prominently among teenagers. Through an analysis of existing legal issues, it was decided that a legal counseling program themed on juvenile delinquency needs to be raised as a preventive effort. The approach used to address juvenile delinquency in Sukomoro Village is advocacy and counseling. This approach was chosen because it is educational and participatory, where the target audience not only receives information but is also actively involved in the process of increasing awareness, understanding, and decision-making to make constructive changes. The outreach activities are conducted dialogically, allowing for a question-and-answer interaction between the speaker and the participants. Technically, the outreach begins with the delivery of material aimed at providing the community with an understanding of the impact of juvenile delinquency, both in the national context and the surrounding environment. A discussion session is held to emphasize the importance of attention to teenagers as the next generation who have a strategic role in national development. Juvenile delinquency itself is a complex social phenomenon influenced by various factors such as minimal parental involvement, weak self-control, negative influences from social interactions, and emotional immaturity. As individuals who are in a transitional phase towards adulthood, teenagers have distinctive characteristics such as high enthusiasm, a great curiosity, and a need for social recognition. Without proper guidance, these characteristics have the potential to develop into deviant behavior.